Pengaruh Kepercayaan Konsumen, Kualitas Informasi Kemudahan Penggunaan, dan Persepsi Resiko Terhadap Minat Beli Konsumen Online: Studi pada Pengguna Aplikasi Shopee di Wilayah Sidoarjo - Naurah Zulfa Salsabila; R. Yuniardi Rusdianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of consumer trust, information quality, ease of use, and risk perception on online consumer buying interest among Shopee application users in the Sidoarjo area. This type of research is quantitative research. The population in this research is shopee application users in the Sidoarjo area. With a sample of 60 respondents taken using a data sampling approach, using the slovin formula by distributing questionnaires. The results of this research show that the F test simultaneously states that Consumer Trust, Quality of Information, Ease of Use, and Risk Perception have a significant influence on Online Consumer Purchase Interest (F-count > F-table). Meanwhile, the t test shows that partially Consumer Trust, Information Quality, Ease of Use, and Risk Perception have a significant influence on Online Consumer Purchase Interest (X1 t-value > t-table; and X2 t-count > t-table).